Battle of Britain - Caine, Michael; Howard, Trevor, 1916-1988.; Jürgens, Curd, 1915-1982.; McShane, Ian, 1942-; More, Kenneth, 1914-1982.; Olivier, Laurence, 1907-1989.; Saltzman, Harry, 1915-; Fisz, S. Benjamin; Hamilton, Guy, 1922-; Kennaway, James, 1928-1968.; Greatorex, Wilfred, 1921-; MGM/UA Home Video (Firm) ([United States] : Metro Goldwyn Meyer Home Entertainment, 2003)
The story of the aerial combat battle of WWII, in which the Royal Air Force held off the German Luftwaffe.
Release date: May. 20, 2003.
Director of photography, Freddie Young ; editor, Bert Bates ; music composed and conducted by Ron Goodwin.
Michael Caine, Trevor Howard, Curt Jurgens, Ian McShane, Kenneth More, Laurence Olivier.
MPAA rating: G.
DVD.
Closed-captioned.
Keywords: Britain, Battle of, Great Britain, 1940 -- Drama; Video recordings for the hearing impaired; Feature films; War films